Pig-heart boy - Blackman, Malorie (London : Collins, 1997)
Pig-heart boy is the story of 13 year old boy's struggle to cope with his problems and lead a normal life.
Keywords: Heart transplantation -- Fiction; Juvenile literature -- Fiction